Evaluating the influence of camera and projector lens distortion in 3D reconstruction quality for fringe projection profilometry (2018)
We study the influence of geometric distortions of the camera and projector lenses on 3D reconstruction quality for fringe projection profilometry. Experimental results on real objects and their 3D models show the accuracy is improved. © 2018 The Author(s).